INOVASI KUKU PALSU BERBAHAN LIMBAH KULIT SINGKONG (Manihot Esculenta) : SOLUSI KREATIF UNTUK KECANTIKAN RAMAH LINGKUNGAN - Mayustina Widyana; Anik Maghfiroh (Universitas Negeri Semarang, 2025)
This study aims to examine the level of attractiveness and consumer acceptance of fake nail innovations made from cassava peel waste (Manihot esculenta) as a creative solution for environmentally friendly beauty products. The research method employed was descriptive quantitative, utilizing a five-point Likert scale questionnaire. The research sample consisted of 23 respondents selected purposively. Assessments were based on four main indicators: aesthetics, texture, eco-friendly appeal, and acceptance of innovative products. Data were analyzed using descriptive statistics to obtain mean scores and interpret rating categories.